Tingkat Fekunditas Nematoda (Meloidogyne spp.) pada Beberapa Tanaman yang Tergolong Familia Solanaceae - DWI RIZKYA WULANDARI; I MADE SUDANA; I DEWA PUTU SINGARSA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
Fecundity of Nematode (Meloidogyne spp.) in Some Plants Belonging to the Solanaceae Family The Solanaceae family is a plants that has a function to meet human food. Although the production of the Solanaceae Family in Indonesia is quite high, it hasnot been able to fulfill the Indonesian Population needs. This is caused by severalfactors and one of them is the attack of pests and diseases that can cause crop failure.Pest that causes a decrease in the Solanaceae family is root bran nematodes,(Meloidogyne spp.) The purpose of the study is to determine the level of penetrationand fecundity of nematodes in several plants belonging to the Solanaceae family, andto obtain species host plants that are less favored than the plants tested Thar can beused as an alternative control of nematoda. This study using a CompletelyRandomized Design (CRD), with 4 types of treatment each using 6 replications with2 research objects to obtain 48 units/plant pots. The results is penetration rate andfecundity rate were highest in tomato plants, then in eggplant plants, chili plants, andthe lowest in cayenne. The result can be used as an alternative to reduce thepopulation of nematoda (Meloidogyne spp.) in the field.